Synaptic Functions of Hemichannels and Pannexons: A Double-Edged Sword - Abudara, Verónica; Retamal, Mauricio A.; Del Rio, Rodrigo; Orellana, Juan A. (Frontiers in Molecular Neuroscience, 2018)
The classical view of synapses as the functional contact between presynaptic and postsynaptic neurons has been challenged in recent years by the emerging regulatory role of glial cells. Astrocytes, traditionally considered merely supportive elements are now recognized as active modulators of synaptic transmission and plasticity at the now so-called “tripartite synapse”. In addition, an increasing body of evidence indicates that beyond immune functions microglia also participate in various processes aimed to shape synaptic plasticity. Release of neuroactive compounds of glial origin, -process known as gliotransmission-, constitute a widespread mechanism through which glial cells can either potentiate or reduce the synaptic strength. The prevailing vision states that gliotransmission depends on an intracellular Ca2+/exocytotic-mediated release; notwithstanding, growing evidence is pointing at hemichannels (connexons) and pannexin channels (pannexons) as alternative non-vesicular routes for gliotransmitters efflux. In concurrence with this novel concept, both connexons and pannexons are known to mediate the transfer of ions and signaling molecules -such as ATP and glutamate- between the cytoplasm and the extracellular milieu. Importantly, recent reports show that glial connexons and pannexons are capable to perceive synaptic activity and to respond to it through changes in their functional state. In this article, we will review the current information supporting the “double edge sword” role of hemichannels and pannexons in the function of central and peripheral synapses. At one end, available data support the idea that these channels are chief components of a feedback control mechanism through which gliotransmitters adjust the synaptic gain in either resting or stimulated conditions. At the other end, we will discuss how the excitotoxic release of gliotransmitters and [Ca2+]i overload linked to the opening of hemichannels/pannexons might impact cell function and survival in the nervous system.